ANALISIS KESULITAN SISWA MENENTUKAN FRASA, UNGKAPAN DAN KATA MAJEMUK SISWA KELAS V SD NEGERI 060936 MEDAN JOHOR TAHUN AJARAN 2020/2021 - nanda tarigan; Pandapotan Tambunan (Universitas Quality, 2021)
This research was conducted because of the difficulties of Grade V students of SD Negeri 060936 Medan Johor in Determining Phrases, expressions and Compound Words. The purpose of this study was to determine the abilities, difficulties and factors causing the students' difficulties in determining phrases, expressions and compound words for the fifth grade students of SD Negeri 060936 Medan Johor. This type of research is descriptive qualitative. This research was conducted in Class V SD Negeri 060936 Medan Johor on 19-20 February 2021. Data collection tools used in this study were multiple choice tests and interviews. Tests are used to determine students' abilities and difficulties, while interviews are used to determine factors that cause student difficulties. Then the data analysis techniques are average and percentage. The population in this study were all fifth grade students of SD Negeri 060936 Medan Johor and also as samples in the study. Based on the data analysis, it was concluded that (1) the students' ability to determine phrases, expressions and compound words of grade V SD Negeri 060936 Medan Johor obtained an average of 49.21 and included in the underprivileged criteria. (2) based on the test questions given the difficulties experienced by students are in the phrase, namely with a percentage of 60.71% and it is included in the high difficulty criteria. As for the difficulties experienced by students, namely, not being able to determine the exact meaning and examples of phrases. (3) the factors that cause student difficulties are the lack of motivation and desire of students in learning Indonesian, the difficulty of students determining phrases, expressions and compound words, the teacher's lack of optimism in teaching material and using media when learning and the lack of parental roles in children's learning.